Protective effects of pomiferin isolated from Maclura pomifera on ischemia-reperfusion injury of rat ovary: biochemical and histopathologic evaluation - Nuri Keleş, Osman; Serkan Erol, Hüseyin; Vural Keleş, Dilek; Karaca, Mehmet; Çakır, Ahmet; Selli, Jale; Koç, Murat; Bünyami Halıcı, Mesut (International Journal of Research in Medical Sciences, 2023)
Background: The aim of this study was to investigate the antioxidant and anti-inflammatory properties of pomiferin, a prenylated flavonoid was purified from Maclura pomifera by thin layer chromatography method, on oxidative stress, sterile inflamation and ovarian tissue damage caused by ischemia-reperfusion model. Methods: Thirty female Wistar albino rats were divided into five groups. In the group CN only laparotomy operation was performed. In group CNPomiferin, rats received 200 mg/kg pomiferin. In group IRVehicle, reperfusion for 3 h performed after an ischemic period of 3 hours. In groups IRPomiferin100 and IRPomiferin200 rats received 100 mg/kg and 200 mg/kg doses of pomiferin, by oral gavage 1 houes before reperfusion. After the experiments, tissue level of malondialdehyde (MDA) and activities of myeloperoxidase (MPO), catalase (CAT), superoxide dismutase (SOD) were determined, and histopathological changes were examined in all rat ovarian tissue. Results: It was determined that irreversible cell damage such as apoptotic and necrotic deaths and reversible cell damage occurred in follicular, endothelial and stromal cells due to oxidative stress in the group IRVehicle. In this group, it was determined that the LPO level exceeded the cellular antioxidant capacity (SOD and CAT enzyme activities) and the PMNL infiltration and activity (MPO), an indicator of sterile inflammation, increased. It was determined that oxidative stress sterile inflammation and irreversible cell damage decreased in a dose-dependent manner with pomiferin treatment. Conclusions: Pomipherin treatment strongly protects ovarian follicles and vascular structures against ischemia-reperfusion injury, thus it may prevent the reduction of ovarian follicle reserve, which is an indicator of female fertility.